2019
DOI: 10.1371/journal.pone.0211401
|View full text |Cite
|
Sign up to set email alerts
|

Cost of illness and program of dengue: A systematic review

Abstract: Background Studies on dengue related to the cost of illness and cost of the program are factors to describe the economic burden of dengue, a neglected disease that has global importance in public health. These studies are often used by health managers in optimizing financial resources. A systematic review of studies estimating the cost of dengue was carried out, comparing the costs between the studies and examining the cost drivers regarding the methodological choices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 44 publications
(86 reference statements)
0
41
0
3
Order By: Relevance
“…Data from Australia, one of the few high income countries with dengue transmission which utilises active surveillance, has shown that rapid notification and case finding enables the minimisation of transmission by triggering public health responses [44]. However, active surveillance systems are expensive and implementation would require a robust cost-benefit analysis [45].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Data from Australia, one of the few high income countries with dengue transmission which utilises active surveillance, has shown that rapid notification and case finding enables the minimisation of transmission by triggering public health responses [44]. However, active surveillance systems are expensive and implementation would require a robust cost-benefit analysis [45].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…And, Brazil spent 20.82 million dollars PPP indirect cost of prevention and control of Aedes aegypti. France, a developed-country, spent 15 million dollars PPP on direct medical-cost of hospitalization [23].…”
Section: Fig 2 Common Aedes Aegypti Breeding-site Including In Malmentioning
confidence: 99%
“…Two such study brought the analyses of the intangible-cost, represented by the Quality-Adjusted Life Years (QALY). In Panama, there had been found an average of 67% QALY during the worst days of illness in 2005 and in Malaysia, the average had been 60% QALY in 2009 [23].…”
Section: Fig 2 Common Aedes Aegypti Breeding-site Including In Malmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from economic burden of disease studies in both economically developed and developing countries continue to be used to advocate for increased investments in health development [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%